The Impact Of Deep Back Massage Method To Pain Intensity And Duration Of Labor On Maternal Inpartu With Active Phase I At Klinik Bersalin Firdaus Banjarmasin - Sismeri Dona; Yayu Puji Lestari; Zahrotul Lubaba Sari (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background : The long duration of labor is one of the factors causing maternal death. The duration of labor of stage I in primipara has a longer duration compared with multiparas. The long duration of labor causes pain last longer so that the mother will being at risk of fatigue which result in emotional response such as anxiety, tension, fear and panic. One way to reduce pain and long duration of labor is the method of deep back massageObjective : To know the impact of deep back massage method to pain intensity and duration of labor on maternal inpartu with active phase I at klinik bersalin firdaus banjarmasin year 2017Methods : This research uses Pre Experimental with 2 designs: Intact Group Comparison and One - Group Pretest-Posttest Design. Statistical test is done by using Paired sample T-test and Mann-Whitney test for the impact of deep back massage method to pain intensity and duration of labor on maternal inpartu with active phase IResult : The result of paired sample t-test shows the value: p = 0,000 (p 0.05) which means there is impact of deep back massage method to pain intensity and Mann-Whitney test shows value: p = 0,000 (p 0,05 ) Which means there is influence of deep back massage method on the duration of labor.Conclusion : From this exsperiment, it can be concluded that deep back massage has an impact to pain intensity and duration of labor on maternal inpartu with active phase i at klinik bersalin firdaus Banjarmasin.Keywords : Deep Back Massage, Intensity Of Pain, Duration Of Labor.